2013
DOI: 10.4236/health.2013.511a2002
|View full text |Cite
|
Sign up to set email alerts
|

Parent and friend influences on the multiple health behavior of Pacific Islander adolescents

Abstract: Youth obesity has increased dramatically in the United States, disproportionally affecting Hawaiian populations. The primary research objective was to describe the influence of parent and friends on the dietary, physical activity, and sedentary behaviors of Pacific Islander high school students. Data were collected from classrooms within a private high school on the Hawaiian island Oahu. Participants were Pacific Islander adolescents attending a high school in Hawaii. Participating adolescents completed a ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Through a university-teacher partnership, students were recruited from two separate high school classrooms. Participating students elicited the participation of one of their parents, resulting in a 74% parent response rate (N=31 parent participants); which is comparable to research among similar youth populations (e.g., Geller, et al, 2013). All participating adolescents were born in the US, majority in Hawai`i.…”
Section: Participants and Settingmentioning
confidence: 64%
See 1 more Smart Citation
“…Through a university-teacher partnership, students were recruited from two separate high school classrooms. Participating students elicited the participation of one of their parents, resulting in a 74% parent response rate (N=31 parent participants); which is comparable to research among similar youth populations (e.g., Geller, et al, 2013). All participating adolescents were born in the US, majority in Hawai`i.…”
Section: Participants and Settingmentioning
confidence: 64%
“…Such youth involvement contributes to tailored intervention efforts while simultaneously expanding participating adolescents' knowledge and skills, increasing their capacity to engage in healthy behaviors (Suleiman, Soleimanpour, & London, 2006). Youth-led research has been published previously among Native Hawai`ian adolescents (Geller, Hendricks, Alvarez, Braceros, & Nigg, 2013). Participating adolescents were expected to report both parent and friend shared time; and, given youth remain dependent on the resources within their home environment, a strong parental influence was expected to emerge for all targeted health behaviors.…”
Section: The Present Studymentioning
confidence: 99%
“…family ties. A study conducted in Hawaiian adolescents revealed that they were more likely to spend sedentary time with parents and active time with friends (21). Indeed, during childhood and the preadolescent years, parental modeling of PA plays a crucial role in lifestyle behavior and establishing a social norm (74).…”
Section: Physical Activitymentioning
confidence: 99%
“…The social environment, which can influence health behaviors like PA and sedentary time, has received increasing attention in recent years (2,3,(15)(16)(17)(18). Influences from family and friends can occur through social pressure, social modeling and imitation, social comparison, and behavior approximation (8,15,(19)(20)(21)(22). For example, studies have highlighted that parental modeling and parental support may be associated with the child's and adolescent's PA (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…Although there is consistent evidence that friends are similar in physical activity; evidence on diet and sedentary behaviour is mixed and limited (Ali, Amialchuk and Heiland, 2011;Geller et al, 2013;Sawka et al, 2013). Friendship networks have been linked to obesity related behaviours; however, network characteristics have not been broadly examined (Sawka et al, 2014).…”
mentioning
confidence: 99%